Forest reclamation of the post-mining dumps. II. Nitrogen fertilization as a key for successful miocene strip-mine dumps reclamation = Rekultywacja leśna hałd pokopalnianych. II. Nawożenie azotowe jako klucz do rekultywacji mioceńskich gruntów pokopalnianych - Drab, Michał; Greinert, Henryk (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The post-mining area in the Łęknica vicinity is covered with Miocene sediments, mainly loamy sands containing pyrite. As part of the reclamation process, described area have been afforested, mainly with Scotch pine. The recultivation results were in many places highly unsatisfactory, because of nutrients deficiency on the trees appearance. A field experiment applying combinations of N, P and K with each element applied at different rates was carried out.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); forest recultivation; dumps reclamation; nitrogen in recultivation; rekultywacja leśna; rekultywacja hałd; azot w rekultywacji